Integrating Cooperative Learning into Organizational Behavior Lessons - Tuan, Luu Trong (Richtmann Publishing, 2011)
This study sought to investigate student diversities in terms of learning styles and academic competence, and the extent to whichstudents change as regards participation, interaction and achievement through Cooperative Learning activities embracing their diversities.77 first-year students from the two Organizational Behavior (OB) classes, one treated as the experimental group (EG) and the other asthe control group (CG), at the School of Business Administration of the International University (IU), a member university of VietnamNational University of Ho Chi Minh City (VNU-HCMC) were invited to participate in the study. The findings substantiated thatVietnamese learners are open to change and teachers should create effective activities for learners to immerse themselves in talkingcooperatively instead of talking individualistically in the classrooms.